A sustainable reduction route of graphene oxide by industrial waste lignin for versatile applications in energy and environment. (20th September 2020) - Jiang, Can; An, Dong; Wang, Zuhao; Zhang, Shumin; An, Xingping; Bo, Jinyu; Yan, Guoping; Moon, Kyoung-Sik; Wong, Chingping
Abstract: The high toxicity of chemical reducing agents for graphene oxide (GO) and the high-polluting emission of industrial waste lignin as black liquor are always the two troubling issues in clean production. Herein, we reported a sustainable win-win route to utilize waste lignin as a green reducing agent of GO through hydrothermal method. Various hydrothermal conditions were investigated to reveal the reduction capability and mechanism of lignin towards GO. Results indicated that lignin could repair the conjugated structure of GO, while the hydroxyl ions in water could cause the decarboxylation of GO. The lignin-reduced GO composites (LRGOs) prepared at acidic and neutral pHs tended to form hydrogels, while the alkaline LRGOs were monodispersed graphene nanosheets in water. The alkaline LRGO suspensions exhibited reversible sol-gel transition by adding acid/base, and irreversible gelation by metal ions chelation. Besides, they could self-assemble into a robust film with excellent mechanical properties (306.7 ± 47.9 MPa in tensile strength, 135.2 ± 45.3 GPa in modulus) and electrical conductivity (399.5 ± 58.3 S/cm) through vacuum filtration and annealing. The freeze-dried LRGO aerogels and their carbonized products showed excellent absorption capacities for various organic solvents. As electrode materials, the LRGO aerogels also displayed a high pseudo-capacitance of 213.8 F/g at 1 A/g. These findings of LRGOs showed a huge application potential in clean energy and environmental pollution treatment. Graphical abstract: Image 1 Highlights: Lignin is proved to be a green, non-toxic and high-efficient reducing agent of GO. Lignin can remove the epoxy groups and repair the conjugated structure of GO. Lignin/RGO dispersions have unique aggregation behavior for water treatment. Annealed LRGO film has a tensile strength of 306 MPa and conductivity of 399.5 S/cm. Lignin/RGO aerogels deliver a high pseudocapacitance of 213.8 F/g at 1 A/g.